Bacterial responses to plant antimicrobials: the case of alkannin and shikonin derivatives - Rat, Angélique; Koletti, Antigoni E.; Rodić, Nebojša; Papageorgiou, Vassilios P.; Willems, Anne; Assimopoulou, Andreana N. (Frontiers in Pharmacology, 2023)
Alkannin, shikonin and their derivatives (A/S) are secondary metabolites produced in the roots of certain plants of the Boraginaceae family such as Lithospermum erythrorhizon Siebold & Zucc. and Alkanna tinctoria (L.) Tausch. These naphthoquinones express anti-cancer, wound healing, and antimicrobial activities. To study the interactions between endophytic bacteria isolated from A. tinctoria and the antimicrobials A/S, endophytic bacteria known to be resistant to the compounds were screened for their effect on A/S in liquid medium. Thereafter, the strain Pseudomonas sp. R-72008, was selected and tested for its ability to modify A/S in nutrient medium and minimal medium with A/S as sole carbon source. Bacterial growth was recorded, and high performance liquid chromatography-diode array and ultra-high performance liquid chromatography-electrospray ionization mass spectrometry analyses were performed to detect and quantify metabolites. In nutrient medium inoculated with R-72008, a decrease in the amount of A/S monomers initially present was observed and correlated with an increase of A/S oligomers. Moreover, a significant decrease of initial A/S monomers in minimal medium was correlated with bacterial growth, showing for the first time that a bacterial strain, Pseudomonas sp. R-72008, was able to use the naphthoquinones A/S as sole carbon source. This study opens new perspectives on the interactions between bacteria and plant antimicrobials.